أنعكاسات عمليات التجارة الالكترونية على هيكل الرقابة الداخلية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
With the growing use of electronic commerce has worked many companies, especially public shareholding to take advantage of them treated in the trade, so that the e-commerce part of the corporate environment, and this has made a career of accounting and auditing facing new challenges to the sophistication of the information and the rapid growth in the market for electronic commerce. And raised many questions about the ability of the audit profession to facing these challenges and how to audit operations of e-commerce and how to give confidence on websites, this sense it has become necessary keep the internal control systems of this technology and what has caused changes to the accounting system, and evolve to fit the developments that have occurred in business and financial environment, and in line with the rapid spread of electronic commerce operations. So the aim of the research to clarify the concept of e-commerce, risks and changes brought about by the internal control system, and determine the implications brought about by e-commerce operations on the internal control system. Among the most important findings of the study that e-commerce has affected and clearly on the components of internal control systems, so needs activity of e-commerce to the concept of internal control for characterized Balastetekih, and objectives of internal control is no different in light of operating electronic data reported under manual operation.Example usage of "":automatically translated by Googleأسفل النموذج